Long-lived cancer-resistant rodents as new model species for cancer research - Azpurua, Jorge; Seluanov, Andrei (Frontiers in Genetics, 2013)
Most rodents are small and short-lived, but several lineages have independently evolved long lifespans without a concomitant increase in body mass. Most notably, the two subterranean species naked mole rat (NMR) and blind mole rat (BMR) which have maximum lifespans of 32 and 21 years respectively. The longevity of these species has sparked interest in the tumor suppression strategies that may have also evolved, because for many rodent species (including mice, rats, guinea pigs, gerbils and hamsters) tumors are major source of late-life mortality. Here, we review the recent literature on anticancer mechanisms in long-lived rodents. Both NMR and BMR seem to have developed tumor defenses that rely on extra-cellular signals. However, while the NMR relies on a form of contact inhibition to suppress growth, the BMR evolved a mechanism mediated by the release of interferon and rapid necrotic cell death. Although both organisms ultimately rely on canonical downstream tumor suppressors (pRB and p53) the studies reveal species can evolve different strategies to achieve tumor-resistance. Importantly, studies of these cancer-resistant rodents may benefit human health if such mechanisms can be activated in human cells.